Actualization of the Thoughts of Prof. Dr. Wahbah al-Zuhailiy in the Sale and Purchase of Stocks Transaction - Nur Wahyudi (UIN Sunan Gunung Djati Bandung, 2020)
This journal presents one of the thoughts of contemporary Islamic scholars, namely Prof. Dr. Wahbah al-Zuhaili. He is known to be very representative in judging every contemporary issue. His thinking is positioned as the basis of sharia for buying and selling shares. An understanding of the law of buying and selling shares will be answered by analyzing the thoughts of Prof. Dr. al-Zuhailiy, which is stated in his book, Al-Mu'Ämalah al-MÄliyah al-Mu'Äshirah. Two questions in this research are: How does Prof. Dr. Wahbah al-Zuhailiy in the sale and purchase of shares? And how is the actualization of the thinking of Prof. Dr. Wahbah al-Zuhailiy in the sale and purchase of shares? Data collection is done using library research as the theoretical basis. After the primary and secondary data are collected, an in-depth analysis of the data sources uses deductive and inductive approaches. The conclusion obtained is that buying and selling shares is analogous to the concept of shirkah and muá¸Ärabah (Muá¸Ärabah musyarÄkah) contracts. In modern language, it is called musharakah mushamah. Actualization of the thoughts of Prof. Dr. Wahbah al-Zuhailiy in buying and selling shares is to provide syar'iy rules in it so that the transaction is legal according to shari'ah.